Evaluating the role of re-adsorption of dissolved Hg2+ during cinnabar dissolution using isotope tracer technique - Jiang, Ping; Li, Yanbin; Liu, Guangliang; Yang, Guidi; Lagos, Leonel; Yin, Yongguang; Gu, Baohua; Jiang, Guibin; Cai, Yong (Journal of hazardous materials, 2016)
[Display omitted] •Develop a new method to study Hg re-adsorption in cinnabar.•Both isotope dilution and tracer techniques were adopted.•The presence of O2 can significantly enhance the dissolution of cinnabar.•Prove the necessity of including re-adsorption in estimating cinnabar dissolution. Cinnabar dissolution is an important factor controlling mercury (Hg) cycling. Recent studies have suggested the co-occurrence of re-adsorption of the released Hg during the course of cinnabar dissolution. However, there is a lack of feasible techniques that can quantitatively assess the amount of Hg re-adsorbed on cinnabar when investigating cinnabar dissolution. In this study, a new method, based on isotope tracing and dilution techniques, was developed to study the role of Hg re-adsorption in cinnabar dissolution. The developed method includes two key components: (1) accurate measurement of both released and spiked Hg in aqueous phase and (2) estimation of re-adsorbed Hg on cinnabar surface via the reduction in spiked 202Hg2+. By adopting the developed method, it was found that the released Hg for trials purged with oxygen could reach several hundred μgL−1, while no significant cinnabar dissolution was detected under anaerobic condition. Cinnabar dissolution rate when considering Hg re-adsorption was approximately 2 times the value calculated solely with the Hg detected in the aqueous phase. These results suggest that ignoring the Hg re-adsorption process can significantly underestimate the importance of cinnabar dissolution, highlighting the necessity of applying the developed method in future cinnabar dissolution studies.